(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
There is emergence of a number of major technology trends impacting the insurance industry, one of these is the rise of social media as a formidable socio cultural force, the implication whereof will be instantaneous.Over the last one decade, social media has been used by people for a number of motives: entertainment, communicating, collaborating, seeking expert advice, sharing information, sharing opinions, etc. Of late, social scientists have observed that social media have increased people’s connectivity and facilitated users’ direct involvement to a great extent.This paper suggests that Social media can be best used by the Insurance Industry for not only reducing operating cost but also incurred claim ratio. To conduct this study, researcher has extracted secondary data from various national and international journals, reports, newspapers articles and websites.